Prévenir le risque infectieux à l’hôpital ? - Eugénie d’Alessandro (Anthropologie & Santé)
In Africa, controlling infectious diseases in hospitals remains a major issue. So far, most analyses have assessed the gap between technical norms and hospital practices. These surveys commonly enlighten a lack of theoretical knowledge and, therefore, come up with cycles of training-assessing which barely improve the situation. An anthropological approach can provide new answers to these problems. A socio-cultural perspective may reveal the hospital as a place where social, ethical, medical and technical dimensions are linked. New tracks have come to light from a survey conducted in the National Hospital of Niamey. First, the superposition of technical and social spaces leads to confusion in gesture. Then, the daily activity in the hospital and the relation between hospital staff and customers are mainly defined by a strong historical inheritance. Last, given different “sensitive words”, technical norms developed within modern medical knowledge become abstract in this particular context.